Comparativo entre centrais telefônicas privadas MD110 e MXONE: fabricante Aastra - Montoia, Fabiana Oliveira (2014)
The objective of this paper is to present a comparison between the telephone exchanges of the brand and its evolution Aastra MD110 MX-ONE, even providing tips to set some facilities. The central MX-ONE has a communication system based on SIP and is designed to run on the Linux platform, the MD110 has worked on a proprietary architecture and their IP's communications were based on H323 protocol.